Challenges for the sequential two-system model of moral judgement. (2nd January 2017) - Gürçay, Burcu; Baron, Jonathan
ABSTRACT: Considerable evidence supports the sequential two-system ("default interventionist") model of moral judgement, as proposed by Greene and others. We tested whether judgement speed and/or personal/impersonal moral dilemmas can predict the kind of moral judgements (utilitarian or deontological) subjects make for each dilemma, and whether personal dilemmas create difficulty in moral judgements. Our results showed that neither personal/impersonal conditions nor spontaneous/thoughtful-reflection conditions were reliable predictors of utilitarian or deontological moral judgements. Yet, we found support for an alternative view, in which, when the two types of responses are in conflict; the resolution of this conflict depends on both the subject and the dilemma. While thinking about this conflict, subjects sometimes change their minds in both directions, as suggested by the data from a mouse-tracking task.